Waste recycling incentives: legal and economic mechanisms - Nukusheva А.А.; Apsimet Н.М.; Rustembekova Д.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
In the context of increasing waste volumes and the need for sustainable development, an effective waste recycling system has become a priority. This study aims to analyze the legal and economic mechanisms that encourage waste recycling to determine the most effective approaches. The research utilizes literature review methods, comparative analysis, statistical data analysis, and case studies. The results of the study indicate that key legal mechanisms include Extended Producer Responsibility (EPR), separate waste collection, recycling quotas, and penalties. An analysis of three EPR models (individual, collective, and mixed) revealed their advantages and disadvantages depending on the specific context. Economic tools, such as subsidies, tax incentives, and environmental fees, provide financial motivation for recycling but require a balanced approach to prevent dependency on government resources and the shifting of costs onto consumers. A comprehensive approach that combines economic and legal mechanisms has proven most effective, as evidenced by the successful experiences of countries with advanced recycling systems. The practical significance of this study lies in its potential application for developing and improving recycling incentive programs across various countries.